Haematological and Biochemical Values of Immunosuppressed BALB/c NUDE and C57BL/6 SCID Mice - Praxedes, Érika Almeida; Pimentel, Muriel Magda Lustosa; dos Santos, Fernanda Araujo; Fernandes, Denilsa Pires; Barbosa, Brenda de Sousa; de Brito, Parmênedes Dias; Gadelha Lelis, Ivana Cristina Nunes; de Macedo, Michelly Fernandes; Bezerra, Marcelo Barbosa (Acta Scientiae Veterinariae, 2018)
Background: The emergence of the NUDE and SCID immunosuppressed mice lineages generated knowledge on various mechanisms of lymphocyte maturation and human autoimmune diseases. Information on haematological and biochemical parameters of these lineages is still scarce, making it impossible to infer homeostasis by comparing data, or to detect genetic influences on the parameters for these species. Haematological and biochemical tests were carried out on Balb/c NUDE and C57BL/6 SCID mice of both sexes, aiming to analyse the presence of genetic influence on possible variations of such parameters and to verify reference values for both lineages. Materials, Methods & Results: One hundred and forty mice (Mus musculus) of the Balb/C NUDE and C57BL/6 SCID lineages were used in the present study. The animals were previously anesthetized, the blood collection procedure was performed by cardiac puncture and the samples were collected in the presence of heparin and intended for haematological and biochemical evaluation, under standardized conditions. The haematological evaluation consisted of red blood cell count, leukocyte counts, platelet counts, haematocrit, haemoglobin concentration, mean corpuscular volume (MCV), and mean corpuscular haemoglobin concentration (MCHC). The quantified biochemical parameters were: urea, creatinine, alanine aminotransaminase (ALT), aspartate aminotransaminase (AST) and alkaline phosphatase (ALP). While analysing the obtained data, it was possible to observe that only females presented divergences (P < 0.05) in the red blood cell series, in haemoglobin and in mean haemoglobin concentration (MCH). Regarding the analysis of the white blood cell series, females only presented differences (P < 0.05) in the leukocyte count. For males, there were variations (P < 0.05) in the counts of leukocytes, eosinophils, lymphocytes and neutrophils. Biochemical tests revealed significant variations (P < 0.05) in ALP and creatinine in females, and ALT, AST and ALP in males. Discussion: As a result of variations due to factors such as genetics, age, diet, sex and environmental conditions, it is of great importance that each research group establishes its own hematological and biochemical reference values for the mice strain used. In this way, possible variations and their causes can be determined, aiding in evaluations of homeostatic and pathological conditions for these animals, as well as their choice and analysis of results obtained in experimental procedures. Thus, the differences found only in females for parameters of the red blood cell series may be due to gene mutations responsible for haematopoiesis or the genetic background. Furthermore, in case of divergences found in the leukocyte parameters, females and males can present different immune responses due to their sex hormones, and females apparently have better performance in these responses. Regarding the other differences found in the leukogram parameters only in males, higher values in the NUDE lineage was attributed to possible stress situations increased by the genetic hormonal factors of the lineage. In addition, a correlation with anaesthetic administration is suggested regarding the variations found in the biochemical parameters, added to the stress generated at the muscular level. In conclusion, this study has presented pioneer values which enable expanding the still scarce knowledge database on immunosuppressed animals, aiding in future studies conducted with the Balb/c NUDE and C57BL/6 SCID lineages.